Theoretical Guidelines for a Psychology of Rural Development (2014)
Many processes related to rural development have a strong psychosocial component. Yet, there exists nospecific psychosocial theoretical framework for addressing them. In this paper, then, we present a set oftheoretical guidelines for analysing rural development processes and interventions from the perspective ofpsychology. In doing so, we draw upon an Actor-Oriented Approach and address concepts commonly usedin rural development studies, such as human agency, social interfaces, worldviews, rationales and strategies,and explore their psychosocial dimensions. This enables us to advance a psychosocial understanding of thecomplexity and multi-determination that characterises processes of rural development, and thus in this wayto add a new perspective to rural development studies.